2022
DOI: 10.1002/slct.202200042
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Conversion of Synthetic Gas to LPG over Hybrid Nanostructure Zeolites Catalysts

Abstract: Recently, Liquified petroleum gas (LPG) attracts wide applications due to its high heating value and clean combustibility. An innovative approach to synthesis of LPG from syngas was established based on Fisher-Tropsch (F-T) technology. However, the conversion and selectivity are generally low with the classical catalysts. The hybrid system of methanol and zeolitebased catalyst was established as a potential approach to promote such a process. To strongly overcome the large demand of LPG and grasp the research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…from carbon-based materials such as fossil fuels, and biomass [ 10 , 11 , 12 , 13 , 14 ]. The syngas can then be used to produce several fuels and chemicals [ 15 ]. The gasification process is usually promoted through a high-temperature reaction (>700 ) using oxygen or steam as an auxiliary component (air gasification or steam gasification) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…from carbon-based materials such as fossil fuels, and biomass [ 10 , 11 , 12 , 13 , 14 ]. The syngas can then be used to produce several fuels and chemicals [ 15 ]. The gasification process is usually promoted through a high-temperature reaction (>700 ) using oxygen or steam as an auxiliary component (air gasification or steam gasification) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fischer-Tropsch synthesis is the best way and main development direction for the conversion of syngas into clean liquid fuels and high value-added chemicals. [1][2][3][4][5] Since Frans Fischer and Hans Tropsch first proposed the Fischer-Tropsch synthesis technology in 1923, the research and development of efficient Fischer-Tropsch synthesis catalysts has been widely concerned. [6,7] The traditional Fischer-Tropsch synthesis is affected by the distribution of ASF(Anderson-Schulz-Flory), and the product distribution is wide.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it has been observed that the increase in the temperature attributes to more gas yield with higher hydrogen contents with the suppression of tar and char concentrations. The obtained syngas could be used to produce several fuels and chemicals. , …”
Section: Introductionmentioning
confidence: 99%
“…The obtained syngas could be used to produce several fuels and chemicals. 33,34 Air and steam are the two most commonly used gasification agents, and several studies have been conducted on the gasification of scrap tires utilizing these gasification agents to analyze their impact on the final product and the overall process. Xiao et al 35 studied the impact of equivalence ratio (ER) on the gas yield using air as a gasification agent.…”
Section: Introductionmentioning
confidence: 99%